Terroir-Driven Efficacy : Harnessing the Chemogeographical Variation in Vetiveria zizanioides Essential Oils for Stage-Specific Management of the Cowpea Weevil (Callosobruchus maculatus F.) - Dyno, Nambavelo; Sambany, Manjovelo Christian; Nicole, Ravelomanantsoa Ramanambe; Koto-Te-Nyiwa, Ngbolua Jean Paul; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2025)
The global reliance on synthetic pesticides for preserving stored cowpea (Vigna unguiculata) seeds is jeopardized by rising insect resistance and food contamination, necessitating urgent exploration of safe, botanical alternatives. This study evaluates the biocidal and repellent potential of essential oils extracted from three geographically distinct Malagasy chemotypes of vetiver (Vetiveria zizanioides) Sambava, Fianarantsoa, and Tsiroamandidy against the devastating stored-product pest, Callosobruchus maculatus F. Chemical profiling revealed distinct compositions, with the Tsiroamandidy essential oil notably enriched in the sesquiterpenoids Khusimol (19.1%) and Zizanoic acid (15.1%). Bioassays demonstrated profound insecticidal effects proportional to concentration (10 to 80μl/l). The oils exhibited rapid fumigant toxicity, with all three chemotypes achieving 100% adult mortality at 60μl/l by 48 hours of exposure. Furthermore, the oils proved to be powerful reproductive inhibitors. Female fertility was completely suppressed at a concentration of 30μl/l, drastically reducing oviposition from the control average of 122 eggs. Most critically, the ovicidal activity was exceptional: the egg hatching rate and subsequent adult emergence (viability) were both completely inhibited (0%) even at the lowest tested dose of 10μl/l (control hatching rate : 82%). Beyond direct lethality, the essential oils demonstrated significant protection through repellency, classifying in the Highly Repellent (Class V) category at concentrations ≥60μl/l. These findings establish regional V. zizanioides essential oils as exceptionally potent, multi-action biopesticides, offering a sustainable and highly effective solution for cowpea preservation.